Factors in Selecting Rental Housing Based on ITERA Student Preferences (International Journal of Architecture and Urbanism, 2023)
The development of higher education institutions in Indonesia is increasing rapidly, one of which is at the Sumatran Institute of Technology or ITERA. One of ITERA’s significant developments is the increase in the number of students. The increasing number of ITERA students certainly impacts increasing the need for supporting facilities around the ITERA campus. One of them is the increasing number of housing needs, in this case, rental housing. Because not a few ITERA students come from outside Lampung Province, rental housing is vital in the ITERA area. The rental housing around the ITERA campus has its type and criteria, so ITERA students have different preferences in choosing rental housing. This study aims to find out what factors are why ITERA students choose rental housing. Research data was collected through a survey process through online questionnaires using a mix-method method, namely a mixture of qualitative and quantitative methods. Meanwhile, data analysis uses content analysis and distribution analysis methods. The research results show a tendency for specific reasons toward the preference for choosing rental housing. ITERA students tend to choose boarding houses for privacy reasons, House in multiple occupation for facilities, and dormitory types for financing reasons. In general, ITERA students tend to choose rental housing for financial reasons.